COMPARATIVE VERIFICATION OF IRRADIATION SET UP BETWEEN EPID SOFTWARE MOSAIQ WITH IVIEWGT IN CONFORMAL RADIOTHERAPY OF NASOPHARYNGEAL CANCER (Radiotherapy Unit Radiology Installation Dr. Sardjito Hospital Yogyakarta) - Syahara Listyawan; Siti Masrochah; Rini Indrati (Poltekkes Kemenkes Semarang, 2018)
Background: Verification of the irradiation set up is a process to ensure that the position and volume of the irradiated tumor is the same as planned. Verification is done by comparing the radiographic image information of the Treatment Planning System (TPS) with radiation therapy to be provided on the Electronic Portal Imaging Device (EPID) device. Existing software on the EPID in doing verification is IViewGT and Mosaiq. Radiotherapist in Radiotherapy Unit Radiology Installation of Dr. Sardjito Hospital Yogyakarta always uses IViewGT software rather than Mosaiq software in performing standard operational procedure verification set up irradiation. The purpose of this study was to describe the verification process, to examine the results of verification and to examine the differences in the results of the verification of set up irradiation between the EPID software Mosaiq with IViewGT in conformal radiotherapy of nasopharyngeal cancer.Methods: The type of research in this thesis is quantitative analytic research. The research was conducted at Radiotherapy Unit Radiology Installation of Dr. Sardjito Hospital Yogyakarta. Data in the form of 52 portal image of nasopharyngeal cancer patients performed conformal radiotherapy. The verification process uses IViewGT and Mosaiq software on the same portal image. Data analysed by Wilcoxon test.Result: The results of the verification is the value of shift set up irradiation on X axis, Y axis and Z axis. Verification using Mosaiq software got the average shift on the X axis of 0 cm, on the Y axis the average value is -0,02 cm, on the Z axis the average value is 0,07 cm. Verification using IViewGT software obtained an average shift on the X axis of 0,02 cm, on the Y axis the average value of 0,03 cm, on the Z axis value averaging 0,02 cmConclusion: The results of this study indicate that there is no difference in verification of irradiation set up between EPID software Mosaiq with IViewGT on X axis with p value 0,361, on Y axis with p value 0,102 and on Z axis with p value 0,199.